Isolation, Characterization, and Genomic Analysis of Pseudomonas sp. Strain SMT-1, an Efficient Fluorene-Degrading Bacterium. (April 2019) - Desta, Mulugeta; Wang, Weiwei; Zhang, Lige; Xu, Ping; Tang, Hongzhi
Comprehensive study of novel microbial organisms capable of degrading fluorene is crucial to develop essential strategies for further application on enhanced bioremediation technologies. Many fluorene-degrading bacteria have been studied; however, little information about the genome sequences of these organisms, which would facilitate investigation of the molecular mechanisms of fluorene degradation, is available. In this study, a bacterial strain designated SMT-1, which uses fluorene as its sole carbon source, was isolated from Laogang landfill in Shanghai, People's Republic of China, and identified as a Pseudomonas sp., based on 16S rRNA gene sequence analysis. Maximum growth and degrading activity of strain SMT-1 were observed at 30°C, pH 7.0 and 200 r/min in mineral salt medium containing 0.4 mm fluorene. We obtained a draft genome sequence of strain SMT-1 to gain insight into the genetic mechanisms for the degradation of aromatic compounds. Sequences greater than 1 kb in length were obtained by Illumina sequencing; strain SMT-1 was found to contain 5542 predicted genes. This working draft genome comprises 68 contigs and DNA scaffolds and has a total size of 6 108 237 bp and a calculated G + C content of 61.59%. Amino acid metabolism clusters were enriched in SMT-1 genes annotation, with the highest abundant observed for the "ABC transporters" subcategories, followed by transcription, energy production and conversion, and inorganic ion transport and metabolism. The genomic information for SMT-1 provides a useful resource for elucidating the molecular mechanism of fluorene catabolism.